2013
DOI: 10.1155/2013/537479
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CαModulates Estrogen-Receptor-Dependent Transcription and Proliferation in Endometrial Cancer Cells

Abstract: Endometrial cancer is the most common invasive gynecologic malignancy in developed countries. The most prevalent endometrioid tumors are linked to excessive estrogen exposure and hyperplasia. However, molecular mechanisms and signaling pathways underlying their etiology and pathophysiology remain poorly understood. We have shown that protein kinase Cα (PKCα) is aberrantly expressed in endometrioid tumors and is an important mediator of endometrial cancer cell survival, proliferation, and invasion. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Most endometrial adenocarcinomas are characterized by positive nuclear estrogen receptor (ER) expression and responsiveness to hormone stimulation. Increasing evidence indicates that prolonged estrogen exposure is associated with initiation of type 1 endometrioid cancers (29)(30)(31). Estrogen exposure was found to result in an overall physiological response within several hours by a genomic mechanism which depends on estrogen binding to nuclear ER resulting in mRNA transcription and protein synthesis of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Most endometrial adenocarcinomas are characterized by positive nuclear estrogen receptor (ER) expression and responsiveness to hormone stimulation. Increasing evidence indicates that prolonged estrogen exposure is associated with initiation of type 1 endometrioid cancers (29)(30)(31). Estrogen exposure was found to result in an overall physiological response within several hours by a genomic mechanism which depends on estrogen binding to nuclear ER resulting in mRNA transcription and protein synthesis of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although these upstream regulators of ERα mainly promote the proliferation of EC, they have also been shown to have some effects on migration (70,71). In addition, protein kinase C α (PKCα) expression stimulates the ligand-independent activation of ER-dependent promoters to enhance the transcriptional capacity of ERα, thereby inducing endometrial proliferation (72). Furthermore, Frigo et al (73) showed that p38 promotes the proliferation of EC cells by stimulating ERα-mediated transcription via phosphorylation of the co-activator glucocorticoid receptor-interacting protein 1.…”
Section: Roles Of Erα In Ecmentioning
confidence: 99%
“…At present, studies have shown that estrogen is involved in the activation of PKC signaling pathway and is an important starting valve for PKC activation [15][16][17]. Does PKC participate in the regulation of estrogen on intestinal glucose absorption?…”
Section: Effect Of Pkc Pathway On Estrogen-mediated Glucose Absorptio...mentioning
confidence: 99%